(untitled) (Terr@ Plural, 2025)
Recently, papers were published on bibliographic surveys on the occurrence of vertebrates and microfossils in the surroundings of the Antarctic Peninsula, but none addressed fossil invertebrates. This paper aims to survey the occurrences of marine Cretaceous invertebrates in Antarctica Peninsula. The better studied invertebrates in the Marambio (Santonian-Maastrichtian), Gustav (Hauterivian-Coniacian), Fossil Bluff (Berriasian-Albian) and Byers (Berriasian-?Santonian) groups are cephalopods (ammonoids and belemnites) and bivalves. The faunas of the mentioned groups are significantly different from each other, but this is possibly due to different paleoenvironmental conditions, incompleteness of the geological record and a lack of studies in some Antarctic regions. Furthermore, in most cases the formations of the aforementioned groups have different ages, which also implies different faunas. We recognized ecological guilds for each stratigraphic group in the Antarctic Cretaceous. Marambio Group has the highest number of guilds, whereas Byers Group has the lowest. Most recognized guilds are composed of epifaunal or nektonic animals and subordinately there are deep infaunal to semi-infaunal invertebrate guilds. We conclude that there are few studies correlating variation in faunal diversity with environmental changes in the Cretaceous of the Antarctic Peninsula. Collections with more refined stratigraphic control of taxa also need to be conducted in all geological units.